Sławomir Augusiewicz, Janusz Jasiński, Tadeusz Oracki, Wybitni Polacy w Królewcu. XVI -XX wiek, pod red. J. Jasińskiego, Littera, Olsztyn 2005, ss. 352. - Piłat, Walenty (Acta Polono-Ruthenica, 2006)
----------